Transforming cancer outcomes in England: earlier and faster diagnoses, pathways to success, and empowering alliances - Harrison CJ; Spencer RG; Shackley DC (Dove Medical Press, 2019)
Christopher J Harrison,1 Roger G Spencer,2 David C Shackley3 1University of Manchester Division of Cancer Sciences, The Christie NHS Foundation Trust, Manchester, UK; 2Chief Executive’s Office, The Christie NHS Foundation Trust, Manchester, UK; 3University of Manchester Division of Cancer Sciences, Greater Manchester Cancer, Manchester, UK Abstract: Cancer outcomes and patient experience in England have never been better but survival remains worse than in comparable countries. Differences in stage at diagnosis and, to a lesser extent, access to optimal treatments are likely to be the most important factors. The national cancer plan emphasizes earlier and faster diagnosis and the creation of cancer alliances providing strategic leadership and coordination. Earlier diagnosis is being promoted by national awareness campaigns designed to overcome fatalism and perceived barriers to consulting a general practitioner as well as improvements to existing screening programs and the introduction of more targeted screening such as Lung Health Checks. These are supported by local social marketing campaigns in which trained volunteers support and advise others about cancer and cancer care. The epidemiology of symptoms in general practice provides an organizing framework for cancer diagnostic pathways. Alliances are implementing a broader model of cancer diagnostic clinics at a larger scale taking into account the different needs of patients with 1) obvious alert symptoms, 2) low risk but not no risk symptoms, and 3) serious but not specific symptoms. Faster diagnosis is being promoted by the introduction of a Faster Diagnosis Standard requiring patients are given a diagnosis of cancer or have it ruled out within 28 days of referral. The three cancer alliances forming the National Cancer Vanguard together with NHS England are publishing clinically led evidence-based Timed Diagnostic Pathways which show how the drastic changes needed can be achieved. Cancer alliances have been successful in developing clinical cancer pathways which need support by improved commissioning and regulatory approaches which align clinical pathways with financial and performance ratings. Clinical leadership has been essential but further focus is needed on making sure that performance and regulatory approaches give proper attention and encouragement to earlier and faster diagnosis. Keywords: cancer, pathways, outcomes, vanguard, diagnosis, rapid